2021
DOI: 10.3390/ijerph18168631
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding after Returning to Work: A Systematic Review and Meta-Analysis

Abstract: Background: The benefits of breastfeeding are widely known; however, continuation after returning to work (RTW) is not. We aimed to conduct a systematic review and meta-analysis to assess the prevalence of breastfeeding after RTW. The secondary objectives were to compare the economic statuses between continents. Method: PubMed, Cochrane Library, Base, and Embase were searched until 1 September 2020, and two independent reviewers selected the studies and collated the data. To be included, articles needed to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 87 publications
1
22
1
Order By: Relevance
“…The previous meta-analysis showed the rate of breastfeeding after returning to work is about 25% which is widely heterogeneous across the world, ranging from 2% to sixty one percent. Interestingly, both economic status and cultural aspect play an important role in the continuation of breastfeeding [ 30 ]. The result of our study found that about 76% (50/65) of mothers were continuing to breastfeed before returning to work but 24% (12/50) had to stop breastfeeding within three months after returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…The previous meta-analysis showed the rate of breastfeeding after returning to work is about 25% which is widely heterogeneous across the world, ranging from 2% to sixty one percent. Interestingly, both economic status and cultural aspect play an important role in the continuation of breastfeeding [ 30 ]. The result of our study found that about 76% (50/65) of mothers were continuing to breastfeed before returning to work but 24% (12/50) had to stop breastfeeding within three months after returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it has been shown that most women have accurate recall of duration of breastfeeding their first baby [ 49 , 50 ], and accordingly we do not believe this type of bias is likely to influence our results systematically. We also did not ask participants when they returned to work, which may influence breastfeeding longevity [ 51 , 52 ]. We also did not address other reasons for discontinuation, such as perception of milk supply, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple factors for the premature abandonment of breastfeeding. Among these factors, we can find the low weight of the infant, the feeling of lack of milk, smoking, the mother's lack of knowledge about breastfeeding or the incorporation to work [14,15]. Education is other of the factors affecting the initiation and continuation of breastfeeding (BF) [9,16,17], and incidentally it is also related to health literacy (HL) [18,19].…”
Section: Introductionmentioning
confidence: 99%